2020
DOI: 10.3390/genes11020226
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Identifies Candidate Tumor Microenvironment and Intracellular Signaling Pathways that Define Tumor Heterogeneity in NF1

Abstract: Neurofibromatosis type 1 (NF1) is a monogenic syndrome that gives rise to numerous symptoms including cognitive impairment, skeletal abnormalities, and growth of benign nerve sheath tumors. Nearly all NF1 patients develop cutaneous neurofibromas (cNFs), which occur on the skin surface, whereas 40–60% of patients develop plexiform neurofibromas (pNFs), which are deeply embedded in the peripheral nerves. Patients with pNFs have a ~10% lifetime chance of these tumors becoming malignant peripheral nerve sheath tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
(101 reference statements)
2
6
0
Order By: Relevance
“…Loss of SUZ12 correlated with NF1 loss, consistent with both genes’ location in the 17.q11.2 genomic locus [ 32 , 45 ]. Additionally, we observed broader copy number gains in chromosome arms 1q, 7p, 8q, 9q, and 17q as well as broad losses in arms 6p and 9p only in MPNST patient plasma, again consistent with previous findings from NF1 MPNST tumors [ 32 , 42 , 46 ] ( Fig 3 ). Finally, while many types of NF1 gene activation can underlie the NF1 disease process, we observed evidence of one of these, NF1 copy number loss, only within MPNST and PN patients, but not in healthy donor controls.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Loss of SUZ12 correlated with NF1 loss, consistent with both genes’ location in the 17.q11.2 genomic locus [ 32 , 45 ]. Additionally, we observed broader copy number gains in chromosome arms 1q, 7p, 8q, 9q, and 17q as well as broad losses in arms 6p and 9p only in MPNST patient plasma, again consistent with previous findings from NF1 MPNST tumors [ 32 , 42 , 46 ] ( Fig 3 ). Finally, while many types of NF1 gene activation can underlie the NF1 disease process, we observed evidence of one of these, NF1 copy number loss, only within MPNST and PN patients, but not in healthy donor controls.…”
Section: Resultssupporting
confidence: 91%
“…Previous tissue-based studies have shown that PN harbor few genome-wide CNAs [ 40 , 41 ] but acquire significant genomic instability during malignant transformation to MPNST [ 32 , 41 , 42 ]. Based on these known significant CNA differences between MPNST and PN tumors, we assumed a large effect size would also be evident comparing MPNST plasma tumor fraction to plasma from PN patients or healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of SUZ12 correlated with NF1 loss, consistent with both genes' location in the 17.q11.2 genomic locus [32,45]. Additionally, we observed broader copy number gains in chromosome arms 1q, 7p, 8q, 9q and 17q as well as broad losses in arms 6p and 9p only in MPNST patient plasma, again consistent with previous findings from NF1 MPNST tumors [32,42,46] (Figure 3). Finally, while many types of NF1 gene activation can underlie the NF1 disease process, we observed evidence of one of these, NF1 copy number loss, only within MPNST and PN patients, but not in healthy donor controls.…”
Section: Genome-wide Cnas From Tumor Are Detected In Plasmasupporting
confidence: 90%
“…Previous tissue-based studies have shown that PN harbor few genome-wide CNAs [40,41] but acquire significant genomic instability during malignant transformation to MPNST [32,41,42]. Based on these known significant CNA differences between MPNST and PN tumors, we assumed a large effect size would also be evident comparing MPNST plasma tumor fraction to plasma from PN patients or healthy controls.…”
Section: Power and Statistical Analysesmentioning
confidence: 99%
“…Bioinformatic deconvolution algorithms from gene expression studies have predicted the microenvironment of MPNSTs to contain activated mast cells, protumor M2-like macrophages, resting CD4+ memory T cells, and cancer-associated fibroblasts. 9 We discuss some recent findings that have been pivotal in shaping our understanding of immune infiltrates in MPNSTs below.…”
Section: Introductionmentioning
confidence: 99%